A characterization of strict Jacobi-Nijenhuis manifolds through the theory of Lie algebroids - Costa, J. M. Nunes da (2002)
We obtain a characterization of strict Jacobi-Nijenhuis structures using the equivalent notions of generalized Lie bialgebroid and Jacobi bialgebroid.